2022
DOI: 10.7759/cureus.27328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the Length of Hospital Stay in Hip Fracture Patients: A Single Centre Study

Abstract: BackgroundHip fracture is a debilitating injury, especially in older individuals, which is associated with significant morbidity and mortality. In recent decades, there has been a great focus on early rehabilitation and discharge after hip fractures. The aim of such efforts is to minimize the financial and clinical burden of this condition. We conducted our study during the COVID-19 pandemic and compared the length of hospital stay (LOS) in 2020 to the LOS in 2019. Additionally, we studied the factors which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Reduction in duration of hospitalization and duration of hospitalization until surgery were other findings raised in our research. Similar to our study, in Northern Ireland, the USA and the East Midlands region of England a shorter length of stay during the pandemic was reported compared to the pre-pandemic period [ 26 28 ]. Also, the shorter time to surgery during the pandemic was a finding that other studies have supported [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Reduction in duration of hospitalization and duration of hospitalization until surgery were other findings raised in our research. Similar to our study, in Northern Ireland, the USA and the East Midlands region of England a shorter length of stay during the pandemic was reported compared to the pre-pandemic period [ 26 28 ]. Also, the shorter time to surgery during the pandemic was a finding that other studies have supported [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with another large population-based study on hip fracture patients, which demonstrated a two-fold increase in length of stay in COVID-19-positive patients. 17 , 48 Notably, multiple studies and a systematic review compared lengths of stay in hip fracture patients before and after the pandemic, and demonstrated reduced lengths of stay, likely due to an attempt to prevent nosocomial viral transmission to the patient or other hospitalized patients. 49 A previous study compared postoperative outcomes of hip fracture patients before and after the pandemic, and found no differences in rates of 30-day hospital readmission and a decrease in rates of patients placed in skilled nursing facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, other studies have demonstrated that LOS was decreased during the pandemic. [26][27][28][29] So the question still remains: how exactly did COVID-19 affect our study, and why was LOS increased post-protocol? It is difficult to precisely measure the effects of COVID-19 on our study, but one possible explanation for the prolonged LOS in the post-protocol group is the difficulty in getting patients discharged to rehabilitation centers (ie SNFs).…”
Section: Discussionmentioning
confidence: 99%